2014
DOI: 10.1002/smll.201303808
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystal Skins with Exciton Funneling for Photosensing

Abstract: gration atop electronic substrates (e.g., using dip coating, spin coating and drop casting), where lattice mismatch problems do not arise. Therefore, these NCs are promising candidates for applications in diverse areas, such as in light-emitting diodes, [ 3 ] solar cells, [ 4 ] and photodetectors [ 5 ] as well as for biolabeling [ 6 ] and biosensing. [ 7 ] Conventional photodetectors using NCs typically operate on the principle of collecting photogenerated charges, where an external bias must be applied for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…Moreover, we estimated the responsivity ( R ) and photogain ( G ), which are critical parameters related to the photodetector sensitivity and can be expressed as:R=InormalpPopt=η(qλhc)Gwhere I p is the photocurrent, P opt is the light intensity power irradiated on the device, η is the external quantum efficiency, h is the Planck's constant, c is the velocity of light in vacuum, q is the electronic charge, and λ is the exciting wavelength . Based on above Equation , the R and G can be estimated to our 11.9 A W –1 and 22.73 under illumination (650 nm, 90 mW cm –2 at bias of –2 V) by assuming η = 1 for simplicity, which is comparable to the values for many previous MoS 2 ‐based photodetectors and some quantum dots photodetectors . The corresponding wavelength‐dependent responsivity was shown in Figure S6, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we estimated the responsivity ( R ) and photogain ( G ), which are critical parameters related to the photodetector sensitivity and can be expressed as:R=InormalpPopt=η(qλhc)Gwhere I p is the photocurrent, P opt is the light intensity power irradiated on the device, η is the external quantum efficiency, h is the Planck's constant, c is the velocity of light in vacuum, q is the electronic charge, and λ is the exciting wavelength . Based on above Equation , the R and G can be estimated to our 11.9 A W –1 and 22.73 under illumination (650 nm, 90 mW cm –2 at bias of –2 V) by assuming η = 1 for simplicity, which is comparable to the values for many previous MoS 2 ‐based photodetectors and some quantum dots photodetectors . The corresponding wavelength‐dependent responsivity was shown in Figure S6, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…However, the electrical performance (e.g., carrier mobility) of the quantum dots (QDs) film is limited due to the sever scattering from a very large number of grain boundaries within the QDs film due to the nanoscale grain size. Moreover, one‐dimensional (1D) material suffers from incomplete surface coverage . So, the ultrathin 2D nanostructures are more conducive to satisfy the requirements of ultrathinness, low‐cost, portability, and mechanical stability in high performance flexile optoelectronic devices …”
Section: Comparison Of the Critical Parameters For The Previously Repmentioning
confidence: 99%
“…Furthermore, NC monolayer of the LS-NS makes the device semi-transparent with sufficient absorption, while reducing the noise generation and dark current. In our other recent work, we also reported that, by using a thick photoactive NC layer, a much lower photovoltage buildup was observed in the LS-NSs and it was attributed to the self-absorption effect [4]. In addition, we demonstrated the sensitivity increase in the LS-NSs via the absorption enhancement of NC film with the integration of plasmonic nanoparticles [5].…”
mentioning
confidence: 87%